PHOTOSHOP ON THE IPAD creativity on the go - De Winter, Rob (NEW RIDERS, 2023)
Adobe Photoshop, the worlds most popular image-editing program, is now available on the iPad. So, wherever you are, you can use familiar Photoshop tools to retouch photos, create compositions, work with layers, add text and a whole lot more. Photoshop on the iPad helps you make the most of Photoshops iPad-optimized interface, as well as combine Photoshop with other familiar Adobe iPad apps, from Lightroom to Fresco. Packed with practical exercises, this guide also offers inspiring interviews with four world-renowned Photoshop artists, Ted Chin, Russell Brown, Frankie Cihi and Magdiel Lopez. Youll see how the pros use Photoshop on the iPad in their workflows, so they can do great work anywhere. And you can too!